Study of different thermal management systems for traction batteries to obtain vehicle lightweighting - Giulia Sandrini; Daniel Chindamo; Marco Gadola; Andrea Candela; Paolo Magri (Heliyon)
Nowadays environmental sustainability is a hot topic, especially with regards to the transportation sector. In fact, political strategies are oriented to the transition towards the cleaner technologies to reduce polluting and climate-altering emissions. However, even fully electric vehicles are not characterized by zero global emissions, due to the production of electricity from sources that are not always renewable. Moreover, this type of vehicle is afflicted by the limited range provided by the battery pack and its long recharging time. So, it is useful to reduce the energy consumption through appropriate strategies, for example by means of the vehicle lightweighting. In this paper we focus on the battery pack lightweighting by considering different passive battery cooling systems as a replacement for the standard active one. The passive systems considered are air and PCM-based (Phase Change Material) cooling systems. In addition to the primary lightweighting given by the replacement of the cooling system, the secondary lightweighting obtained by reducing the capacity of the battery pack to return to the range of the starting reference vehicle has been also considered. Three tools were used for the study: VI-CarRealTime and another consolidate vehicle model to obtain the power demand on a standard driving cycle; and an ad-hoc battery system model, configurable according to the cooling system. The simulations showed that the air-cooled system leads to greater lightweighting, but it makes the battery cells work far from 20 °C (optimal operating temperature) and therefore it could lead to greater battery cell degradation and its field of application must be limited to vehicles operating in fleets, with predictable mission; this can be overcome by using an appropriate PCM-based cooling system, stearyl alcohol. Furthermore, using a PCM, glycerol, with a melting point close to the optimal operating temperature of the batteries, allows to reduce the cell degradation.